Propofol inhibits oxidative stress injury through the glycogen synthase kinase 3 beta/nuclear factor erythroid 2-related factor 2/heme oxygenase-1 signaling pathway. Issue 1 (1st January 2022) - Zhang, Ziyin; Yan, BaoFeng; Li, Yuguo; Yang, Shuo; Li, Jinfeng
ABSTRACT: Oxidative stress is the main cause of ischemia/reperfusion injury. Propofol is a commonly used intravenous hypnotic anesthetic agent with antioxidant properties. In this study, we aimed to elucidate the protective effects of propofol on H2 O2 -induced cardiomyocyte injury and myocardial ischemic/reperfusion injury (MIRI) in rats. Cardiomyocyte injury was evaluated by determining cardiac troponin-1 (cTn-1) and creatine kinase-MB (CK-MB) levels. Antioxidative stress was assessed by measuring lactate dehydrogenase (LDH), malondialdehyde (MDA), glutathione (GSH), superoxide dismutase (SOD), reactive oxygen species (ROS), and catalase (CAT) levels. Apoptosis was evaluated using flow cytometry and TUNEL assays. Bax and Bcl-2 expression levels were determined by quantitative reverse transcription PCR (qRT-PCR) and Western blotting. The levels of glycogen synthase kinase 3 beta/nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) pathway-related factors were measured using Western blotting. Myocardial infarction in rats was analyzed using an Evans blue staining assay. The results showed that propofol reduced the levels of CK-MB, cTn-1, LDH, MDA, and ROS, and increased the levels of GSH, SOD, and CAT in H2 O2 -treated H9c2 cells. Additionally, propofol inhibited H2 O2 -induced apoptosis by downregulating Bax and upregulating Bcl-2. Moreover, propofol decreased the area of myocardial infarction in rats with MIRI. The GSK3β-Nrf2/HO-1 signaling pathway was activated by propofol. Rescue experiments showed that Nrf2 knockdown alleviated the effects of propofol on oxidative stress and apoptosis in H9c2 cells. In conclusion, propofol attenuated H2 O2 -induced myocardial cell injury by regulating the GSK3β/Nrf2/HO-1 signaling pathway and alleviating MIRI, suggesting that propofol is a promising therapeutic option for ischemic heart disease.